The Simpatie project (Italian Journal of Public Health, 2005)
In this article a current European multi-national project in patient safety is described. This project began in Feb. 2005 and will run for two years. It is managed by a consortium of seven NGO’s led by the CBO (Dutch Institute for Healthcare Improvement) and receives 60%of its funding from DGSANCO (the health and social policy division of the European Commission).The policy framework within which the project evolved is also described. Despite the constraints of Art 152 of the Treaty, support from Commissioner Byrne encouraged a High Level Reflection process (HLRP) on patient mobility and healthcare developments in the EU, which started in June 2002 and involved European Health Ministers.As a result a series of very positive recommendations were made at the end of 2003 which subsequently were accepted and have affected policy direction in a number of areas e.g. co-operation on e-health, better use of resources as well as quality issues such as patient safety and quality implications of cross-border patient flows.The paper then reviews current issues in patient safety activity within Europe. Finally the Simpatie project is described. It is comprised of four main elements. First, a mapping exercise to determine the present status of patient safety activity within at least 20 European countries.It utilises extensive existing networks within and between the members of the consortium and other relevant stakeholders within Europe.Secondly, a “tool-box” exercise attempts to define common terminology and an expert consensus on measurement tools. This is complemented by the third element, a strategy component which aims to define the basic elements of different approaches to implementing patient safety within health systems. Finally, the last element is dissemination, where involvement of both public and health user organisations will be an important component.
Keywords: Patient safety; Europe; patient mobility; quality; Simpatie; mapping; expert consensus; strategy and dissemination